1995
DOI: 10.1126/science.7770774
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Purple Acid Phosphatase Containing a Dinuclear Fe(III)-Zn(II) Active Site

Abstract: Kidney bean purple acid phosphatase (KBPAP) is an Fe(III)-Zn(II) metalloenzyme resembling the mammalian Fe(III)-Fe(II) purple acid phosphatases. The structure of the homodimeric 111-kilodalton KBPAP was determined at a resolution of 2.9 angstroms. The enzyme contains two domains in each subunit. The active site is located in the carboxyl-terminal domain at the carboxy end of two sandwiched beta alpha beta alpha beta motifs. The two metal ions are 3.1 angstroms apart and bridged monodentately by Asp164. The iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
378
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 434 publications
(398 citation statements)
references
References 22 publications
17
378
0
3
Order By: Relevance
“…Perhaps a water molecule transfers a proton to the leaving group. The proposed mechanism for 5NTs resembles that suggested for the related TRAPs based on structural and many spectroscopic data [299,309]. This includes a direct transfer of the phosphoryl group to the water nucleophile without the formation of a covalent intermediate.…”
Section: Domain Movementsupporting
confidence: 54%
See 1 more Smart Citation
“…Perhaps a water molecule transfers a proton to the leaving group. The proposed mechanism for 5NTs resembles that suggested for the related TRAPs based on structural and many spectroscopic data [299,309]. This includes a direct transfer of the phosphoryl group to the water nucleophile without the formation of a covalent intermediate.…”
Section: Domain Movementsupporting
confidence: 54%
“…The first structure of an enzyme of this superfamily was determined for a plant purple acid phosphatase [299], which is homologous to mammalian tartrate-resistant acid phosphatases. The core fold of the catalytic domain of these enzymes is a four-layered αββα structure.…”
Section: Protein Structurementioning
confidence: 99%
“…116 RKBPAP is a larger enzyme than the mammalian PAPs (111 kDa dimer) and contains Fe(III)-Zn(II) at the active site instead of Fe(III)-Fe(II). Only 3.1 Å separate the two metal ions at the active site of RKBPAP and the amino acid residues that provide the metal ligands are conserved across all known members of the PAP family.…”
Section: Enzyme Mechanism and Conservation Of Trap-like Enzymes From mentioning
confidence: 99%
“…Crystal structures have been reported for PAPs isolated from pig uterus, also known as uteroferrin or Uf ( Figure 1) (14), rat bone (15), and red kidney bean (16,17). All PAPs bear an active site comprising a ferric ion (site A) and a divalent metal ion (site B).…”
mentioning
confidence: 99%
“…However, direct evidence for the exact number of waterbased ligands present in this active form is lacking. Red kidney bean (Fe III -Zn II ) PAP is the only member of this family to have been characterized crystallographically in its oxoanion-free form (16,17), but the resolution of these structures was too low to locate any terminal or bridging water-based ligands. Recent ENDOR spectroscopic studies (21) have suggested that U f in its phosphate-free reduced form bears a single terminal aqua/hydroxo ligand coordinated to the Fe II ion, but the ferric site is five coordinate.…”
mentioning
confidence: 99%